2006
DOI: 10.1073/pnas.0510232103
|View full text |Cite
|
Sign up to set email alerts
|

Identification of pulmonary Oct-4 + stem/progenitor cells and demonstration of their susceptibility to SARS coronavirus (SARS-CoV) infection in vitro

Abstract: In this study, we report a serum-free culture system for primary neonatal pulmonary cells that can support the growth of octamerbinding transcription factor 4 ؉ (Oct-4 ؉ ) epithelial colonies with a surrounding mesenchymal stroma. In addition to Oct-4, these cells also express other stem cell markers such as stage-specific embryonic antigen 1 (SSEA-1), stem cell antigen 1 (Sca-1), and Clara cell secretion protein (CCSP) but not c-Kit, CD34, and p63, indicating that they represent a subpopulation of Clara cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
159
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(172 citation statements)
references
References 43 publications
9
159
1
3
Order By: Relevance
“…28 Although there is not a full overlap between human and mouse stem cell antigens, human lung cancer CD133 þ cells and mouse bronchoalveolar stem cells share to some extent the expression of the stem cell markers CD34, BCRP1, Oct4 and the absence of pan-hematopoietic (CD45) and -endothelial (CD31) antigens. 16,24 Moreover, we observed that the rare CD133 þ cells present in the mouse lung increase considerably following naphthalene-induced injury, in line with the possibility that CD133 may be expressed in mouse bronchoalveolar stem cells. In contrast, the bronchoalveolar stem cell and alveolar type 2 cell marker SP-C showed a variable expression in lung cancer spheres, reflecting the phenotypic variability of human lung cancer stem cells.…”
Section: Discussionsupporting
confidence: 76%
“…28 Although there is not a full overlap between human and mouse stem cell antigens, human lung cancer CD133 þ cells and mouse bronchoalveolar stem cells share to some extent the expression of the stem cell markers CD34, BCRP1, Oct4 and the absence of pan-hematopoietic (CD45) and -endothelial (CD31) antigens. 16,24 Moreover, we observed that the rare CD133 þ cells present in the mouse lung increase considerably following naphthalene-induced injury, in line with the possibility that CD133 may be expressed in mouse bronchoalveolar stem cells. In contrast, the bronchoalveolar stem cell and alveolar type 2 cell marker SP-C showed a variable expression in lung cancer spheres, reflecting the phenotypic variability of human lung cancer stem cells.…”
Section: Discussionsupporting
confidence: 76%
“…A population of stem cells that express markers of ESC/epiblast/PGC cells was recently described in several nonhematopoietic organs, for example, in epidermis (Dyce et al, 2004(Dyce et al, , 2006Yu et al, 2006), bronchial epithelium (Ling et al, 2006), myocardium, pancreas, (Kruse et al, 2006;Danner et al, 2007), testis (Kanatsu-Shinohara et al, 2004;Guan et al, 2006), retina (Koso et al, 2006), and amniotic fluid (De Coppi et al, 2007). This finding supports a concept of developmental deposition of Oct-4 ϩ EPSC in developing organs.…”
Section: Oct-4 ؉ Stem Cells In Other Tissuessupporting
confidence: 77%
“…The regulatory networks controlling the function of ES cells, including key regulators of ES cell maintenance, namely Nanog, Oct4 and Sox2 [16,17], are also found in some adult stem cell populations [18,19]. Moreover, genes associated with ES cell identity have been linked to tumor histology, supporting the possibility that these genes contribute to the stem cell-like phenotype of many tumors [20].…”
Section: Introductionmentioning
confidence: 98%